Panoscopic alloying of cobalt in CeO2-ZrO2 solid solutions for superior oxygen-storage capacity - Song, Seung Hak; Moon, Jooho; Kim, Jeong Hun; Hong, Jongsup; Lee, Jong-Ho; Lee, Hae-Weon; Kim, Byung-Kook; Kim, Hyoungchul (PERGAMON-ELSEVIER SCIENCE LTD, 2016)
Oxygen processes (reduction and evolution) play a central role in a variety of physical and chemical applications to meet the growing demands for energy and environmental protection. However, the discovery and optimization of such functional materials are great challenges because they are still hampered by material inherencies and thermodynamic limits. Here, we demonstrate the fabrication of a novel material structure via atomistic doping and nanoscale compositing, a panoscopic alloying powder (PAP) of cobalt in a CeO2-ZrO2 solid solution. This novel structure possesses superior oxygen-storage capacity (OSC) and improved structural stability because it retains the best features of both transition metal oxides and ceria-based ceramics. According to the thermogravimetry and dilatometry measurements of a 10 mol% PAP sample, (Ce0.65Co0.10)Zr0.25O2-delta, at 800 degrees C under cyclic reduction-oxidation, an OSC of 2312 mu mol-O g(-1) was successfully obtained with negligible structural change and a linear strain of 1%. (C) 2016 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.
Keywords: CERIA; OXIDES; OXIDATION; CEO2; CO; CATALYSTS; MN; CU